Giant Anterior Chest Wall Basal Cell Carcinoma: An Approach to Palliative Reconstruction - Pauline Joy F. Santos; Christina Prendergast; Amber Leis (Case Reports in Oncological Medicine)
Anterior chest wall giant basal cell carcinoma (GBCC) is a rare skin malignancy that requires a multidisciplinary treatment approach. This case report demonstrates the challenges of anterior chest wall GBCC reconstruction for the purpose of palliative therapy in a 72-year-old female. Surgical resection of the lesion included the manubrium and upper four ribs. The defect was closed with bilateral pectoral advancement flaps, FlexHD, and pedicled VRAM. The palliative nature of this case made hybrid reconstruction more appropriate than rigid sternal reconstruction. In advanced metastatic cancers, the ultimate goals should be to avoid risk for infection and provide adequate coverage for the defect.